High PD-L1 expression on immune cells along with increased density of tumor-infiltrating lymphocytes predicts a favorable survival outcome for patients with loco-regionally advanced head and neck cancer: early results from a prospective study - Blažek, Tomáš; Petráš, Marek; Hurník, Pavel; Matoušek, Petr; Knybel, Lukáš; Čermáková, Zuzana Zděblová; Štembírek, Jan; Cvek, Jakub; Soumarová, Renata (Frontiers in Oncology, 2024)
Introduction In the era of personalized medicine and treatment optimization, use of immune biomarkers holds promise for estimating the prognosis of patients with head and neck squamous cell carcinoma (HNSCC) undergoing definitive treatment. Methods To evaluate the prognostic potential of immune biomarkers, we conducted a prospective monocentric cohort study with loco-regionally advanced HNSCC patients indicated for definitive radiotherapy/radiochemotherapy at the Department of Oncology, Ostrava University Hospital, Czech Republic, between June 2020 and August 2023. We focused on the expression of programmed death ligand 1 (PD-L1) and tumor-infiltrating lymphocytes (TILs) relative to overall survival (OS) and specific survival rates. Associations between biomarkers and survival rates were assessed by crude and adjusted hazard ratios (cHR, aHR, respectively) obtained from Cox proportional hazards regression. Results Among a total of 55 patients within a median follow-up of 19.7 months, there were 21 (38.2%) all-cause deaths and 15 (27.3%) cancer-related deaths. An overall survival (OS) rate of 61.8% and a disease-specific survival (DSS) rate of 72.7% were recorded. A significant association between survival rates and a ≥10% difference in PD-L1 expression on immune versus tumor cells (high PD-L1IC expression) was documented regardless of the type of analysis (univariate or multivariate). In addition, a stronger association was confirmed for OS and the composite biomarker high PD-L1IC expression along with either median-higher CD8+ TIL count or increased TIL density ≥30%, as indicated by an aHR of 0.08 (95% CI, 0.01 to 0.52) and 0.07 (95% CI, 0.01 to 0.46), respectively. Similar results were demonstrated for other specific survival rates. Discussion The early outcomes of the present study suggest the utility of a strong prognostic factor involving a composite biomarker high PD-L1IC expression along with increased TIL density in HNSCC patients undergoing definitive radiotherapy and radiochemotherapy. Trial registration The study is registered with Clinicaltrials.gov. – NCT05941676